177k views
5 votes
I need the fourth term of one and three all I need is the answers so I can quiz my son.

I need the fourth term of one and three all I need is the answers so I can quiz my-example-1

1 Answer

1 vote

The formula for the nth term is expressed as

an = (an - 1)^2 - 3

This is a recursive formula

This means that the second term, a2 is

a2 = (a2 - 1)^2 - 3

a2 = (a1)^2 - 3

a2 = 4^2 - 3 = 16 - 3 = 13

a3 = (a3 - 1)^2 - 3

a3 = (a2)^2 - 3

a3 = 13^2 - 3 = 169 - 3 = 166

a4 = (a4 - 1)^2 - 3

a4 = (a3)^2 - 3

a4 = 166^2 - 3 = 27556 - 3 = 27553

Thus,

a4 = 27553

User SyntaxVoid
by
3.4k points